CONTROLE DO MOFO BRANCO: EFEITO DE PONTAS E VOLUMES DE PULVERIZAÇÃO EM SOJA E PRODUTOS BIOLÓGICOS EM SOJA E CANOLA - Berger Neto, Ayrton (2015)
The fungus Sclerotinia sclerotiorum (lib.) de Bary causes the disease called white mold, with more than 400 species of host plants. The fungus produces resistance structures, sclerotia, which remain viable in the soil for more than 5 years. For these reasons, the control of the pathogen is very difficult. It is necessary to the management of the disease, using cultural, biological and chemical control simultaneously. In order to get the best spraying technology for the chemical control of white mold in Paraná, two experiments were made in soybeans. The first in Ivaí-PR (2012/13), in fatorial design (2 x 3) +1, two spraying volumes, 100 and 200 L ha-1 and three nozzles, hollow cone, flat fan and low drift venture-type nozzle, in the spraying of fluazinam, and more the control treatment. And another in Mauá da Serra-PR, in season 2013/14, was fatorial design (2x2x3) +1, two spraying volumes, 100 and 200 L ha-1, two fungicides, fluazinam and procimidone, and also three nozzles, hollow cone, flat fan and low drift venture-type nozzle, and more the control treatment. Evaluations of incidence, severity, sclerotia production and yield were made in each of the trials. In both of years no interaction was observed between the factors in the most part of the evaluations. The lowest incidence was observed in low drift venture-type nozzle. In the evaluation of production of sclerotia, in two years, the flat fan and low drift venture-type nozzle presented lower values than the hollow cone. The fungicide procimidone provided reduced production of sclerotia compared to fluazinam. There was no difference between 100 and 200 L ha-1 in the control of white mold in soybean. It is concluded that the low drift venture-type nozzle can be used for control of white mold in soybean, reducing evaporation of droplets and drift, which reduces environment pollution. Three trials were made of biological control of white mold in soybean, one in 2012/13, in Mauá da Serra-PR, and two in 2013/14, one in Arapoti-PR and another in Mauá da Serra-PR. It was also carried out an experiment in biological control of white mold in the oil seed rape in 2013, in Arapoti-PR. All biological control experiments were used the biological control agents (BCA) Thichoderma harzianum SC; Thichoderma asperellum WG; Bacillus subtilis and Coniothyrium minitans compared with a control treatment and a fungicide treatment. Evaluations of incidence, severity, sclerotia production, yield, and viability assessments of sclerotia from soil were made. All BCA, used in ideal conditions, were able to reduce viability of sclerotia from soil. The BCA were able to reduco incidence, severity and sclerotia production compared to Control treatment, in both crops, soybean and oil seed rape, but were inferior to treatment with fungicides. The BCA are an effective tool in the management of white mold, in the summer and in the winter. The BCA can reduce the viability of sclerotia from soil and can reduce the occurrence of the pathogen in the host plants.